2018
DOI: 10.1186/s40248-018-0121-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining the social status, risk factors and lifestyle changes of tuberculosis patients in Sri Lanka during the treatment period: a cross-sectional study

Abstract: BackgroundTuberculosis (TB) is a major global health problem, commonly seen in underdeveloped countries. The probability of contracting the disease is significantly higher among the economically vulnerable and the socially disadvantaged. Risk factors associated with TB can also change over time. In the Sri Lankan context, no study has explored how these factors impact patients. Therefore, we aimed to explore social status, associated risk factors and lifestyle changes during the treatment period of TB patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…As in similar studies [36,37], mortality and morbidity from TB in our study were higher in men. Although in some studies, older people showed higher risks of TB-related morbidity and mortality [36], in our study, no significant relationship was found between age and the mortality rate. This finding can be explained by the fact that the mean age of the people with TB who died in every county was entered into our analysis, and that the mean values for age by county were closely distributed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As in similar studies [36,37], mortality and morbidity from TB in our study were higher in men. Although in some studies, older people showed higher risks of TB-related morbidity and mortality [36], in our study, no significant relationship was found between age and the mortality rate. This finding can be explained by the fact that the mean age of the people with TB who died in every county was entered into our analysis, and that the mean values for age by county were closely distributed.…”
Section: Discussionsupporting
confidence: 89%
“…Among the limitations of this study, it should be noted that this study had an observational design, and that more studies are therefore needed to assess causal effects and the real impact of risk factors. Additionally, similar studies found significant relationships of alcohol drinking and smoking with TB incidence [36], but information on those variables was not recorded in our data set, making it impossible for us to examine these relationships. Furthermore, in this study we used a GEE-based ZINB model to determine the related risk factors.…”
Section: Discussionmentioning
confidence: 96%
“…The main limitation of the study is that it was conducted only in one DM clinic which caters for a group of patients belong to middle and lower socio-economic groups in the country. However, considering the fact that PTB is known to be common among such socio- economic groups in Sri Lanka [ 42 ], the estimate of the proportion of PTB among DM is not likely to be an underestimate. In addition, majority of the study sample was females, whereas PTB is commoner among males in Sri Lanka [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study the incidence of pulmonary tuberculosis which mostly occurs in the productive age due to a number of risk factors including infections of Mycobacterium, direct contact with the patient, the level of socio-economic conditions seen by economic status with UMR as gold standard but according to (Senanayake et al, 2018). Low socioeconomic status negatively affected the lifestyle and social interactions of patients during the treatment period.…”
Section: Methodsmentioning
confidence: 96%